Inter-vehicle communications - achieving safety in a distributed wireless environment. Challenges, systems and protocols - Torrent Moreno, Marc (KIT Scientific Publishing, 2007)
This thesis contributes to the development of inter-vehicle communications with the goal of enhancing vehicular active safety. The wireless technology IEEE 802.11p is analyzed with an extended network simulator. As a result, challenges and design criteria for vehicular communication systems are defined. Finally, strategies for channel congestion avoidance and information dissemination are proposed, constituting a robust design to cope with unreliable and saturated wireless channel conditions.